Analysis of the January Effect in Time Series of Mexican Stock Market Indexes - Garay Alvarado, Mariana; Demmler, Michael (Mercados y Negocios, 2019)
The current article has the research objective to search for empirical evidence of the January effect within the time series of the IPC and the sector indexes of the Mexican stock market using econometric GARCH analysis. The dataset is formed by the log returns of the daily closing prices corresponding to the IPC as well as the sector indexes covering the period from 01/01/2010 to 12/31/2018. The main results of the article are as follows: Based on the January effect the Efficient Market Hypothesis in its weak form sense cannot be rejected for the Mexican stock market as the results do not provide significant evidence of the existence of the respective calendar anomaly within the analyzed time series of the IPC and the different sector indexes.